2014
DOI: 10.1038/nchembio.1640
|View full text |Cite
|
Sign up to set email alerts
|

A self-adjuvanting vaccine induces cytotoxic T lymphocytes that suppress allergy

Abstract: Epitope-based peptide vaccines encompass minimal immunogenic regions of protein antigens to allow stimulation of precisely targeted adaptive immune responses. However, because efficacy is largely determined by the functional status of antigen-presenting cells (APCs) that acquire and present peptides to cells of the adaptive immune system, adjuvant compounds are needed to enhance immunogenicity. We present here a vaccine consisting of an allergen-derived peptide conjugated to a prodrug of the natural killer-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 57 publications
1
78
0
Order By: Relevance
“…Promising early results have been observed in preclinical and clinical studies, particularly in infectious disease (1,2), cancer (3)(4)(5), allergy (6)(7)(8), and autoimmune disease applications (9,10). Several classes of agents are currently being evaluated for their ability to stimulate or repress immunity, but few are as versatile as nucleic acids.…”
mentioning
confidence: 99%
“…Promising early results have been observed in preclinical and clinical studies, particularly in infectious disease (1,2), cancer (3)(4)(5), allergy (6)(7)(8), and autoimmune disease applications (9,10). Several classes of agents are currently being evaluated for their ability to stimulate or repress immunity, but few are as versatile as nucleic acids.…”
mentioning
confidence: 99%
“…Use of this model was necessary to enable a precise quantitation of allergen-specific, IL-4-and IL-13-producing CD4 þ T cells in the lung. Importantly, the conditions for adoptive transfer experiments were chosen to closely recapitulate findings in normal C57BL/6 or PKO mice primed with allergen to elicit a Th2 response, and vaccinated with DC þ allergen peptides 7 (Figure 1) or a-Gal-Cer-peptide conjugates 14 to elicit a CTL response. In all cases, allergenspecific CTLs were found to mediate suppression of airway inflammation, whereas CTLs of irrelevant specificity had a modest or undetectable effect.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] We focused our study on allergen-specific CTLs as they are profoundly inhibitory, and they could potentially form the basis of allergen-specific immunotherapies. Our previous work showed that Ag-specific CTLs can inhibit the priming of naïve CD4 þ T cells in vivo, 21 and that their cytotoxic function is critical to their ability to inhibit allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid chromatography-tandem mass spectrometry (LC-MS/MS) is an analytical technique with high selectivity and sensitivity able to detect and quantify analytes such as pharmaceutical actives and excipients [11] that has been used to analyse the chemical synthesis of α-GalCer and analogues [12]. The multiple reaction monitoring (MRM) mode of the tandem mass spectrometer allows for high selectivity by measuring the unique fragmented species of the original molecule.…”
mentioning
confidence: 99%